‘A trusted person is cursed’. Trust as an accountability mechanism in the Somali collective response to crises - Ahmed Musa; Cindy Horst (Fennia: International Journal of Geography)
A wide range of actors respond to humanitarian crises, including those present in or socially embedded in the local context. How are local responders held accountable by those who provide them with funds to support collective responses to crisis, and by those they provide assistance to? We answer this question through empirical research on collective crisis responses during droughts in Somaliland. Somaliland is a self-declared republic in the northern region of Somalia, seeking international recognition and functioning with its own government and institutions since 1991. In Somaliland, social security is rarely provided by the state, but is rather supplied within kinship- and locality-based networks, which also play a central role in times of crisis. We argue that elaborate accountability systems exist, embedded in social practice. These systems are built on long-term relationships and are more holistic in scope than narrowly defined technical-financial understandings of accountability common in international humanitarianism. Drawing on literature on trust and our empirical research, we argue that locally-embedded humanitarianism needs to be understood from a relational ethical perspective. In Somali collective crisis response, accountability practices are upheld collectively. They are built and maintained through reciprocity and individuals fulfilling expectations, thus further cementing existing social relations. Informal accountability measures to sanction an abuse of trust in this context serve to strengthen the social support system rather than punish individual wrongdoings. Wrongdoers are thought to receive their punishment through being cursed, face the wrath of God, and societal condemnation.